Prescribing practices of corticosteroids in outpatient dermatology department of Injibara General Hospital, north-West Ethiopia, 2024 - Tegegnie, Alemu Bezabih; Alene, Tamiru; Tamir, Workineh; Sineshaw, Meaza Molla (Frontiers in Medicine, 2025)
BackgroundCorticosteroids are among the most frequently prescribed drugs in the world because they are extremely effective for the relief of symptoms of many inflammatory and immune disorders and other conditions. Corticosteroids have been a mainstay of pharmacotherapy in dermatological practice.ObjectiveThis study aimed to assess prescribing practices of corticosteroids in outpatient dermatology department of Injibara General Hospital, North-West Ethiopia, 2024.MethodA facility-based retrospective cross-sectional study was conducted from September 1 to September 10, 2024, with 422 patient prescriptions issued at the dermatology outpatient department of Injibara General Hospital containing at least one corticosteroid medicine. All patient prescriptions dispensed from the dermatology outpatient department from April to August 2024 containing at least one corticosteroid medicine were included. A structured data collection tool was used to collect data, and Statistical Package for Social Science version 27.1 was used for data analysis. The study population was characterized through descriptive analysis.ResultsFemale patients accounted 54.2% of the cases recorded, and the most common age group was between 21 and 30 years (26.5%). Atopic dermatitis (15.4%) was the most common skin disorder, followed by papular urticaria (9.97%) and seborrheic dermatitis (8.9%) for which corticosteroids were prescribed. Topical corticosteroids were the most commonly prescribed medications, accounting for 94.1%. The percentage of corticosteroids prescribed by generic name was 82.4%. We found that the percentage of topical corticosteroid prescriptions in fixed drug combinations and extemporaneous prescription was 4.4 and 1.2%, respectively. Mometasone furoate was the most commonly prescribed (34.6%), followed by clobetasol propionate (26.7%). Ointments (53%) followed by creams (40.6%) were the most common formulations of topical corticosteroids issued. In the present study, moderate potency TCS were most commonly prescribed (32.3%), followed by high potency (28.3%), and super high potency (27.6%), respectively.ConclusionFrom this study, it can be concluded that atopic dermatitis is the most common skin disease observed in the studied dermatology outpatient where the corticosteroid was indicated. Mometasone furoate and clobetasol propionate were the two most commonly prescribed agents. Prescribing practice of high potent and very high potent topical corticosteroids was found to be considerably high.